CO2 emissions from drained calcareous organic soil profiles from the Mästermyr area - Siggelin, Erik (SLU/Dept. of Soil and Environment, 2017)
Peatlands in their natural state are in general considered as net sinks of greenhouse gases over time, with the accumulation of dead organic matter as peat. Drained organic soils have been of importance for Swedish agriculture for more than a century. On the island Gotland, drained organic soils are in general fertile and are used to grow high value crops such as carrots and are important in fodder production due to their higher resistance to summer droughts. Decomposition of the organic material and release of greenhouse gas occur when organic soils are drained, but there is a considerable variation in emissions and subsidence rate between different organic soils. The knowledge about drained organic soils with high marl and calcium carbonate content is limited. The aim of this work is to examine if there is a variation in CO2 emissions from different types of organic soils with a high calcareous content. The aim is also to study if the CO2 emissions rate can be correlated with any soil properties. Undisturbed soil samples were collected from three sites at the Mästermyr peat-land area both from the topsoil and the subsoil. The different topsoil types were fen peat, marly peat and peaty marl. Four conclusions that could be made in this work are (1) the CO2 emissions vary between different soil types. (2) That all soils increase their CO2 emissions when they are drained but at a different degree and they reach a maximum between 25 cm and 75 cm drainage depth. (3) An increase of air filled pore space was positively correlated with CO2 emissions in the subsoil but not in the topsoil. (4) There was a positive correlation between loss on ignition and CO2 emissions for all soils in this study.